2019
DOI: 10.1093/mnras/stz495
|View full text |Cite
|
Sign up to set email alerts
|

Orientation effects on the near-infrared broad-band emission of quasars

Abstract: We recently proposed the equivalent width (EW) of the narrow [OIII]5007Å emission line as an orientation indicator for active galactic nuclei. We tested this method on about 12,300 optically selected broad line quasars from the SDSS 7th Data Release at redshift z < 0.8 and with full width at half-maximum values of broad emission lines (Hα, Hβ, and Mg ii) larger than 2000 km/s. We now examine their spectral energy distributions (SEDs) using broad band photometry from the near-infrared to the ultraviolet to look… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…The results indicate no obvious correlations. It means the mid-infrared emission from jet contribution is weak in radio-loud quasars which is consistent with the view of Bisogni et al (2019), and implies that the emission of radio-loud quasars in mid-infrared band is dominated by the thermal emission from dusty torus.…”
Section: The Relation Between the Variability Amplitude In Mid-infrar...supporting
confidence: 83%
See 1 more Smart Citation
“…The results indicate no obvious correlations. It means the mid-infrared emission from jet contribution is weak in radio-loud quasars which is consistent with the view of Bisogni et al (2019), and implies that the emission of radio-loud quasars in mid-infrared band is dominated by the thermal emission from dusty torus.…”
Section: The Relation Between the Variability Amplitude In Mid-infrar...supporting
confidence: 83%
“…Mao et al (2018) showed γray blazars had larger mid-IR variability than non-γ-ray blazars. Bisogni et al (2019) showed the infrared bump cannot be induced by synchrotron emission form the blazar-like objects, and found no difference between radio quiet and radio-loud objects in the stacked mid-infrared spectral energy distribution. Rakshit et al (2019) found a positive correlation between the variability amplitude and 1.4 GHz radio power by analyzing 63 radio-detected Narrow Line Seyfert 1 galaxies.…”
Section: The Relation Between the Variability Amplitude In Mid-infrar...mentioning
confidence: 96%
“…We are planning to apply a correction for the disc inclination with respect to the line of sight by making use of the rest-frame equivalent width of the [O iii] emission line, EW[O iii], for the sources for which this line is available in SDSS (z < 0.8). This quantity has been proposed by our group as an orientation indicator of the accretion disc (Risaliti et al 2011;Bisogni et al 2017bBisogni et al , 2019. We will further analyse this aspect in a future work.…”
Section: Additional Contributions To the Dispersionmentioning
confidence: 90%
“…Recent study by Bisogni et al (2019) shows that the low EW[O III] sources are face-on view and have more flatter IR/optical SED compared to the high EW[O III] sources, which have edge-on view with respect to the observer. They also claim that their finding suggest the torus to be clumpy.…”
Section: Advanced Torus Modelsmentioning
confidence: 99%